Wpływ konkordatu między Stolicą Apostolską a Rzecząpospolitą Polską z 1993 roku na nowelizację Kodeksu rodzinnego i opiekuńczego z 1964 roku - Włodarczyk-Czech, Edyta (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article on the influence of the 1993 Concordat on the amendment of the Family and Guardianship Law of 1964 at the end of the 1990s is intended to demonstrate that this influence was significant in terms of the institution of marriage and the institution of separation. The possibility for a marriage entered under the internal law of a church or other religious association to obtain civil law effects is a significant and socially expected change. Undoubtedly, the signing of the Concordat made it much easier for people who wanted to give this institution both a secular and a religious dimension to get married. On the other hand, the institution of separation of spouses in Polish and canon law, despite the apparent similarity in its essence, is characterized by significant differences in both legal systems. Polish law does not indicate the specific reasons for the separation, focusing only on the complete breakdown of the marriage, while canon law does not treat the complete breakdown of the partnership as a sine qua non condition, but pays attention to the primary causes of this breakdown. In Polish law, separation is not intended to permanently separate the spouses, but is a space for reflection and reflection on continuing in marriage. In canon law, it is mainly intended to protect the innocent party and children and allows separation from an adulterous spouse. However, when circumstances improve, or forgiveness simply ceases.
Keywords: concordat; Catholic Church; marriage; separation; family and guardianship law